Structural and electronic investigation of ZnO nanostructures synthesized under different environments - Bhardwaj, R.; Bharti, A.; Singh, J.P.; Chae, K.H.; Goyal, N.; Gautam, S. (Cell Press, 2018)
An explicit study of comparison on the basis of structure and electronic properties of ZnO nanostructures was discussed. ZnO synthesized by sol-gel and hydrothermal method without using any surfactant leads to the formation of two different morphologies. Rietveld crystal structure refinement of X-ray diffraction patterns confirmed the wurtzite structure of both samples. Raman spectra also confirmed the wurtzite phase formation and improved crystallinity in sample synthesized by hydrothermal route that are concurrent with results obtained from X-ray diffraction. Field-emission scanning electron microscopy revealed the formation of ZnO spherical nanoparticle structure for sol-gel method and flower like μ-structure for ZnO prepared through hydrothermal route. Williamson-Hall equations applied to study the strain and stress parameters present in the material, show the decrease in their values as the crystal size increases. Energy band gap is calculated using diffused reflectance spectroscopy. Near-edge X-ray absorption fine-structure measurements at O K- and Zn L3,2- edges simulated with FEFF9.05 code confirmed the presence of oxygen vacancies. Further extended x-ray absorption fine-structure revealed a similar local atomic structure for both samples despite having different morphologies. ？ 2018 The Authors